Does Farmers’ Trust in Their Stakeholders Influence the Sustainability of Value Chains? Evidence from Cashew Nut Farmers in Tanzania - Norbert Musa Njelekela; Leonada Raphael Mwagike; Edward Bahati Makoye (Universitas Airlangga, 2026)
Background: Despite the prevalence of trust as an important relational governance mechanism in agrifood value chains, previous studies have overlooked its influence on their sustainability, as assessed using the triple bottom line (TBL). Using stakeholder (ST) and Resource Dependency theory (RDT) as theoretical lenses, benevolence and credibility as trust antecedents, and their influence on TBL were assessed, as they have not been explored in the literature. That stands as a novel contribution that enriches the existing scholarly discourse. Objective: This study aims to investigate how farmers' trust toward stakeholders, as reflected in the dimensions of benevolence and credibility, shapes the sustainability of cashew value chains in a developing-country context. Method: A cross-sectional design using a single key informant was used to gather data from 387 cashew nut farmers using a structured questionnaire. The collected data were examined through Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the proposed hypotheses. Results: Of the six hypothesized relations (H1 to H6), H1, H4, H5, and H6 had a positive (+) and significant (P ≤ 0.05) influence on sustainability dimensions, except for H2 and H3, which had positive (+) but not significant (P ≥ 0.05) relationships with sustainability dimensions. Conclusion: Trust is an important governance mechanism for achieving sustainability in cashew nut value chains. Benevolent did not have positive relations with both environmental and social dimensions, hence, attention is needed. Practically, stakeholders with a role in regulating the cashew industry should consider trust as an important factor for achieving sustainability. Keywords: Benevolence; credibility; value chain; sustainability; Tanzania